A defective mutant of Salmonella enterica Serovar Gallinarum in cobalamin biosynthesis is avirulent in chickens - Paiva,Jacqueline Boldrin de (2009)
Salmonella enterica serovar Gallinarum (SG) is a fowl typhoid agent in chickens and is a severe disease with worldwide economic impact as its mortality may reach up to 80%. It is one of a small group of serovars that typically produces typhoid-like infections in a narrow range of host species and which therefore represents a good model for human typhoid. The survival mechanisms are not considered to be virulent mechanisms but are essential for the life of the bacterium. Mutants of Salmonella Gallinarum containing defective genes, related to cobalamin biosynthesis and which Salmonella spp. has to be produced to survive when it is in an anaerobic environment, were produced in this study. Salmonella Gallinarum is an intracellular parasite. Therefore, this study could provide information about whether vitamin B12 biosynthesis might be essential to its survival in the host. The results showed that the singular deletion in cbiA or cobS genes did not interfere in the life of Salmonella Gallinarum in the host, perhaps because single deletion is not enough to impede vitamin B12 biosynthesis. It was noticed that diluted SG mutants with single deletion produced higher mortality than the wild strain of SG. When double mutation was carried out, the Salmonella Gallinarum mutant was unable to provoke mortality in susceptible chickens. This work showed that B12 biosynthesis is a very important step in the metabolism of Salmonella Gallinarum during the infection of the chickens. Further research on bacterium physiology should be carried out to elucidate the events described in this research and to assess the mutant as a vaccine strain.